A data envelopment analysis of the impact of European funds on environmental indicators - Ferasso, Marcos (2021)
The European Union (EU) has launched two regional investment programs of European Funds (FE) in the last decade. One covers the period of 2007 to 2013, and the second from 2014 to 2020. Among the goals contained in FE regulations is that of achieving sustainable growth through the conversion of fossil energy production systems to renewable energy. This research has had a goal to determine whether the countries of the Eurozone maintain homogeneous levels of efficiency in the use of these resources to improve the levels of environmental quality related to the use of this type of energy. The adopted research method for efficiency analyses was Data Envelopment Analysis (DEA). Findings revealed that the efficiency in the use of renewable energies is very uneven among the analyzed countries and that these differences are maintained throughout the analyzed period. These results suggest that the criteria for the distribution of the funds should be modified. The current distribution is mainly based on the per capita income of the countries and/or regions. In this way, compliance with the European Green Pact approved in September 2020 would be guaranteed.